Low Resistivity and High Carrier Concentration in SnO2 Thin Films: The Impact of Nitrogen–Hydrogen Annealing Treatments - Qi-Zhen Chen; Zhi-Xuan Zhang; Wan-Qiang Fu; Jing-Ru Duan; Yu-Xin Yang; Chao-Nan Chen; Shui-Yang Lien (Nanomaterials, 2025)
The tin dioxide (SnO2) thin films in this work were prepared by using plasma-enhanced atomic layer deposition (PEALD), and a systematic analysis was conducted to evaluate the influence of post-deposition annealing at various temperatures in a nitrogen–hydrogen mixed atmosphere on their surface morphology, optical behavior, and electrical performance. The SnO2 films were characterized by using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Hall effect measurements. With increasing annealing temperatures, the SnO2 films exhibited enhanced crystallinity, a higher oxygen vacancy (OV) peak area ratio, and improved mobility and carrier concentration. These enhancements make the annealed SnO2 films highly suitable as electron transport layers (ETLs) in perovskite solar cells (PSCs), providing practical guidance for the design of high-performance PSCs.